Fiscal Policy and Financial Development - Hauner, David (IMF Working Papers; Working Paper ;, 2006)
We examine the effects of public sector borrowing from the domestic banking system on financial development in middle-income countries. While these countries' external debt has been falling, the share of bank credit absorbed by the public sector has been rising rapidly. We argue that this runs the risk of slowing financial development by affecting structural characteristics of the banking systems. We find empirical evidence that too much public sector borrowing harms financial deepening, and that banks mainly lending to the public sector tend to be more profitable but less efficient. We note that these effects add to the costs of fiscal prolificacy.